2022
DOI: 10.4103/jfmpc.jfmpc_1780_21
|View full text |Cite
|
Sign up to set email alerts
|

A study to assess the outcome in COVID-19 confirmed cases receiving Remdesivir as compared to conventional therapy: Medical records-based audit

Abstract: Introduction: COVID-19 infection caused by SARS-Corona virus-2 (SARS-CoV-2) has caused large number of infections and mortality globally. There are no proven medications to prevent and treat COVID-19, nevertheless several potential pharmacotherapeutic agents have been tried. Remdesivir was found to be effective in few studies. Aims: To assess the outcome in COVID-19 confirmed cases receiving Remdesivir as compared to conventional therapy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
3

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
0
3
Order By: Relevance
“…In most [23][24][25], but not all [26] the observational studies, the 30-day mortality and/or disease progression rates among patients treated with remdesivir for 5 days were higher than those in our study, at around 12-13%. In a recently published Greek study, a 10% mortality rate was reported in three Greek hospitals (4% in 14 days), with a 9-day mean interval between admission and recovery [27].…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…In most [23][24][25], but not all [26] the observational studies, the 30-day mortality and/or disease progression rates among patients treated with remdesivir for 5 days were higher than those in our study, at around 12-13%. In a recently published Greek study, a 10% mortality rate was reported in three Greek hospitals (4% in 14 days), with a 9-day mean interval between admission and recovery [27].…”
Section: Discussioncontrasting
confidence: 80%
“…In a multicenter international study using data from both an open-label trial and a real-world cohort, the rates of recovery at 14 days since admission were slightly lower (74.4%) compared to those observed in our study (80.9%) [ 22 ]. In most [ 23 , 24 , 25 ], but not all [ 26 ] the observational studies, the 30-day mortality and/or disease progression rates among patients treated with remdesivir for 5 days were higher than those in our study, at around 12–13%. In a recently published Greek study, a 10% mortality rate was reported in three Greek hospitals (4% in 14 days), with a 9-day mean interval between admission and recovery [ 27 ].…”
Section: Discussioncontrasting
confidence: 71%
“…However, 30-days mortality (3.8%) was lower than that in the ACTT-1 (11%), WHO's Solidarity (15%) and DisCoVeRy (8%) trials (9,12,21). In most (22)(23)(24) but not all (25) observational studies 30-days mortality and/or disease progression rates in patients treated with 5day remdesivir were higher than in our study being around 12-13%. In a recently published Greek study, a 10% mortality rate was reported in three Greek hospitals (4% in 14 days), with a 9-day mean interval between admission and recovery [26].…”
Section: Discussioncontrasting
confidence: 76%